Gamelan Reog Ponorogo Accompaniment as a Symbol of Communication in The Power of Javanese Leadership - Deniawan Tommy Chandra Wijaya; Christa Wongsodikromo (Javanologi: International Journal of Javanese Studies, 2024)
This research focuses its analysis on how the Reog Ponorogo gamelan instruments is able to represent symbols communication of Javanese leadership power. The research is a type of field research, and was conducted in three regions, namely Surakarta, Magetan, and Ponorogo. The research method was conducted in an interpretive qualitative way, with a symbolic interpretive approach technique that bases its analysis on the interpretation and meaning of cultural symbols, which are expressed through the interaction of taste, emotionality, spirituality, rationality and morality in the communication process. For this reason, in conducting research, researchers combine data from the findings of data in the field, with theories and literature data related to the object of research. Data collection efforts are carried out interactively through in-depth interview methods, and are carried out continuously until they reach data saturation. As for the determination of sources, researchers used purposive sampling technique, which is a sampling technique based on certain considerations. The results of the study found three powers of Javanese leadership, namely the power of authority, the power of wisdom or kawicaksanan, and the spiritual power or kawaskithan represented in the accompaniment of Reog Ponorogo music. All of these lead to the concept of Panaragan, or the concept of understanding one's identity.Keywords: Warok, Reog Ponorogo, Panaragan, Javanese Leadership